Peran Guru dalam Pembentukan Karakter Disiplin Santri: Perspektif Adab al-'Alim wa al-Muta'allim - Moch. Nahrowi; Thohir (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Discipline character formation is an essential component of pesantren education, particularly in responding to social changes and technological developments that influence students’ behavior. This study aims to analyze the role of teachers in shaping the disciplinary character of santri at Tanwirul Ulum Islamic Boarding School, Paleran, Umbulsari, Jember, through the perspective of Adab al-'Alim wa al-Muta'allim by KH. M. Hasyim Asy'ari. This study employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation involving pesantren administrators, teachers, santri, parents, and supporting staff. Data were analyzed through data reduction, data display, and conclusion drawing, with source and method triangulation employed to ensure data credibility. The findings indicate that teachers play a significant role in developing santri’s disciplinary character through exemplary conduct, habituation, supervision, and individualized guidance. The internalization of the values of Adab al-'Alim wa al-Muta'allim is reflected in the development of time discipline, eating etiquette, and sleep discipline. This character formation is supported by the pesantren’s regulatory system and family involvement, while the main challenges include overlapping activities, external environmental influences, mobile phone use, and peer habits. These findings demonstrate that the internalization of ethical values through teacher modeling and habituation can strengthen santri’s disciplinary character in a sustainable manner